2020
DOI: 10.2196/17980
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Virtual Reality in Managing Acute Pain and Anxiety for Medical Inpatients: Systematic Review

Abstract: Background Virtual reality is increasingly being utilized by clinicians to facilitate analgesia and anxiolysis within an inpatient setting. There is however, a lack of a clinically relevant review to guide its use for this purpose. Objective To systematically review the current evidence for the efficacy of virtual reality as an analgesic in the management of acute pain and anxiolysis in an inpatient setting. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 73 publications
8
94
2
3
Order By: Relevance
“…Indeed, only a mean of 1.2 mg and 1.1 mg were needed on top of the initial bolus in the VR and control groups, respectively. Overall, our results are in line with the literature [ 24 ]. In a recent systematic review, Smith et al [ 24 ] suggested that VR was effective for analgesia in a variety of different clinical settings but could also have disadvantages.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, only a mean of 1.2 mg and 1.1 mg were needed on top of the initial bolus in the VR and control groups, respectively. Overall, our results are in line with the literature [ 24 ]. In a recent systematic review, Smith et al [ 24 ] suggested that VR was effective for analgesia in a variety of different clinical settings but could also have disadvantages.…”
Section: Discussionsupporting
confidence: 93%
“…The Gate Control, Multiple Resource, and Neuromatrix Theories of Pain explain the mechanism of action of VR in pain reduction. These theories purport that pain is influenced by sensory, affective, and cognitive inputs (Basil, 1994;Indovina et al, 2018;Smith et al, 2020). Since the human brain has a finite processing capacity, VR saturates the brain with engaging positive stimuli thus blocking/distracting from the pain signals resulting in pain reduction (Kahneman, 1973;Eccleston, 1999Eccleston, , 2001Hoffman et al, 2007Hoffman et al, , 2011Tack, 2019;Hoffman, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 20% of the world's population lives in chronic pain (Goldberg and McGee, 2011) and 17.6% of those in chronic pain in the U.S. rate their pain as severe (Nahin, 2015;Becker et al, 2017). Traditional treatments for pain have relied on medications, in particular opioids, or invasive interventions, such as nerve blocks or epidural injections, each with their own risk profile (Benyamin et al, 2008;Bellini and Barbieri, 2013;Jung et al, 2014;Teater, 2014;Webster, 2017;Liberman et al, 2019;Chuan et al, 2020;Smith et al, 2020). In light of the current opioid overdose death crisis, there is an urgent need for implementation of noninvasive complementary and alternative modalities for the treatment of pain, both acute and chronic.…”
Section: Introductionmentioning
confidence: 99%
“…Although the previously mentioned technical requirements can be fulfilled by increased research knowledge, there are still some relevant concerns related to both ethical and regulatory aspects that jeopardize the road to clinic of this "game changer" technology [1,2].…”
Section: Ethical Issues and Commercialization Regulatory Aspectsmentioning
confidence: 99%
“…The development of new revolutionary technologies during recent years, such as the use of Big Data, virtual reality systems and three-dimensional (3D) bioprinting, has created great expectations in the scientific community, not only regarding the improvement of the quality of life in patients affected by devastating pathologies, but also in terms of saving health-care associated resources [1][2][3]. In this regard, 3D bioprinting is an emerging manufacturing technology which holds great promise for a wide variety of biomedical applications, including drug testing, pathophysiological studies and regenerative medicine [4].…”
Section: Introductionmentioning
confidence: 99%